Moralność zawodowa nauczyciela – dydaktyka, wychowawcy, opiekuna - Szewczak, Iwona (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The figure of a teacher represents the main tool for realisation of didactic, educational and protective functions of school. Tasks, which are put in front of teacher at present time, are unusually important, with requirements towards him or her being often too demanding . In order to live up to them, the teacher needs proper (technical and moral) expertise. A question of teacher’s professional ethos or moral attitude to vocational work also has been brought up in the article. Needless to say, without these, the realisation of basic teacher’s functions is almost impossible to conduct. The genesis of teacher’s professional morality and its scope were both presented, justfying the need of implementation of the elements of vocational ethics in the teaching process within school education.